1993
DOI: 10.1006/bojl.1993.1029
|View full text |Cite
|
Sign up to set email alerts
|

Apostasiads, systematic anatomy, and the origins of Orchidaceae

Abstract: Botanical Journal of the Linnean Society 111 (1993) 411-455. doi:10.1006/bojl.1993.1029Received by publisher: 0000-01-01Harvest Date: 2016-01-04 12:20:29DOI: 10.1006/bojl.1993.1029Page Range: 411-45

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 6 publications
1
15
0
1
Order By: Relevance
“…Mycobionts in this subfamily have been overlooked until recently. Stern et al (1993) fi rst reported the occurrence of coils of fungal hyphae in cortical cells of roots in A. nuda R. Br. Furthermore, septate hyphae and pelotons (coil of hyphae in living cortical cells) in root tubercles of A. wallichii R. Br.…”
Section: Fungal Colonization -Cortical Cells Of Root Tubercles Inmentioning
confidence: 99%
“…Mycobionts in this subfamily have been overlooked until recently. Stern et al (1993) fi rst reported the occurrence of coils of fungal hyphae in cortical cells of roots in A. nuda R. Br. Furthermore, septate hyphae and pelotons (coil of hyphae in living cortical cells) in root tubercles of A. wallichii R. Br.…”
Section: Fungal Colonization -Cortical Cells Of Root Tubercles Inmentioning
confidence: 99%
“…The taxonomic placement of the genera Apostasia and Neuwiedia, here referred to as apostasiads (Lindley, 1853), has been controversial, as summarized in *To whom correspondence should be sent. 0024-4074/93/010087 f 0 8 $08.00/0 87 0 1 9 9 3 The Linnean Society of London detail by Stern, Cheadle & Thorsch (1993). The two genera are usually considered within Orchidaceae (Burns-Balogh & Funk, 1986;Cronquist, 198 1 ; de Vogel, 1969;Dressler, 1981Dressler, , 1986Garay, 1960;Takhtajan, 1969Takhtajan, , 1980, although some systematists have placed them in their own family (or families), e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Apostasia is usually considered to be most closely related to Neuwiedia (Dressler, 1981(Dressler, , 1986Apostasioideae), but it has sometimes been linked with the Cypripedioideae (see Burns-Balogh & Funk, 1986). Our goal in this investigation is to consider, from a phylogenetic standpoint, the anatomical data recently acquired by Stern et al (1993), along with available morphological data, in order to address the systematic questions posed in recent literature on Orchidaceae. We are especially interested in the phylogenetic placement of Apostasia.…”
Section: Introductionmentioning
confidence: 99%
“…The apostasioid orchids-Neuwiedia and Apostasia-have been regarded as either closest relatives to orchids or the most basal orchids by taxonomists and orchid experts since the first species of Apostasia was discovered (see Stern, Cheadle, and Thorsch [1993] for a thorough review of the classification history of the group). Few taxonomists (e.g., Hutchinson, 1973) have placed apostasioids outside an orchidaceous group at family or ordinal level.…”
mentioning
confidence: 99%
“…This could be because he was working with fragments of herbarium specimens that may have been poorly preserved. The first notion of mycorrhiza in apostasioids seems to be by Stern, Cheadle, and Thorsch (1993) who mentioned the ''occurrence of coils of fungal hyphae in some cortical cells of some species'' and depicted infected cortical root cells of Apostasia wallichii. Stern and Warcup (1994) reported and illustrated infections by septate hyphae in root-tubercles of this species, but protocorms have so far not been observed from this group of orchids.…”
mentioning
confidence: 99%